Arte precolombinista y Arte Histórico - Ávila Salas, Marjorie (2013)
The following essay tries to show how the Central American art produces during some parts of its History an art with pre-Colombian reminiscence which, according to the Freud’s Theory of Psychoanalysis, means a confrontation with an historical Latino American psychological trauma caused by the Hispanic Conquest and in consequence, a social liberation.